The Implementation of PBL Model by Using Demonstration Toward Problem Solving Skill and Student Learning Outcome - Solekhan, Ziki; Supardi, Kasmadi Imam; Wardani, Sri (Journal of Primary Education)
This research aims to find out differences between PBL model by using demonstration to PBL model by using expository method toward problem solving skill and Primary School student ? affective learning achievement. This True experimental research was used with post-test only control group design. This research was used PBL with demonstration method given to experimental group and PBL with expository method given to control group. The data collection in this research was used observation, test, questionnaire, and documentation. The data analysis was used t-test. Based on the data analysis of this research, it revealed two data of problem solving skill and affective learning outcome with sig score (2 tailed) 0.000 < 0.05. Based on the already determined criteria of the test, then H0 was denied while  was accepted. showed there was average difference of problem solving skill and affective learning outcome of both groups with 81.36 for experimental group and 62.20 for control group. Meanwhile, the affective learning achievement of experimental group was 0.59 and control group was 0.18. Therefore, it could be concluded that there was difference of problem solving skill and student ? affective learning outcome by using PBL with demonstration method to PBL with expository method.